Analysis of temporally evolved nanoparticle-protein corona highlighted the potential ability of gold nanoparticles to stably interact with proteins and influence the major biochemical pathways in Brassica juncea - Prakash, Satya (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.